Genome-wide Hi-C Analyses in Wild-Type and Mutants Reveal High-Resolution Chromatin Interactions in Arabidopsis - Feng, Suhua; Cokus, Shawn J.; Schubert, Veit; Zhai, Jixian; Pellegrini, Matteo; Jacobsen, Steven E. (Molecular cell, 2014)
Chromosomes form 3D structures that are critical to the regulation of cellular and genetic processes. Here, we present a study of global chromatin interaction patterns in Arabidopsis thaliana. Our genome-wide approach confirmed interactions that were previously observed by other methods as well as uncovered long-range interactions such as those among small heterochromatic regions embedded in euchromatic arms. We also found that interactions are correlated with various epigenetic marks that are localized in active or silenced chromatin. Arabidopsis chromosomes do not contain large local interactive domains that resemble the topological domains described in animals but, instead, contain relatively small interactive regions scattered around the genome that contain H3K27me3 or H3K9me2. We generated interaction maps in mutants that are defective in specific epigenetic pathways and found altered interaction patterns that correlate with changes in the epigenome. These analyses provide further insights into molecular mechanisms of epigenetic regulation of the genome. [Display omitted] •Chromatins interact through pericentromeres, telomeres, and adjacent regions•Interactive heterochromatic islands (IHIs) show strong long-range interactions•Interactions are correlated with epigenetic marks in active or silenced chromatins•Mutants in repressive epigenetic pathways alter chromatin-interaction patterns Using Hi-C analysis, Feng et al. show extensive interactions among regions of Arabidopsis chromatin. These interactions correlate with epigenetic marks, and mutants of epigenetic pathways affect interaction patterns.